An Examination of Denomination-Level Efforts in Congregation Health Programming - Bopp, Melissa (Journal of religion and health, 2019)
Large denominational faith-based organizations (FBOs, e.g., conferences, dioceses) have potential to impact population health, though current activities are largely unknown. This study examined how large denominational FBOs approach health promotion programming and relevant barriers and issues related to capacity. A self-report survey via email and mail collected responses from representatives of FBOs about their health programming. The sample (n = 154) was diverse and included Catholic, Presbyterian, and Lutheran traditions. The most common activities were inclusion of health-related topics at organizational events and the provision of educational resources. Working with FBOs at a macro-level has potential implications for population-level health improvements.